Analysis of Agricultural Land Changes on the Spatial Pattern of Langkat Regency - Agung Supriadi; Abdi Sugiarto; Cut Nuraini (Journal of Information Technology, computer science and Electrical Engineering, 2025)
This study aims to examine the Analysis of Agricultural Land Change on the Spatial Pattern of Lalat Regency. Inthis research, the researcher uses a descriptive research method with a qualitative approach. The purpose of thisdescriptive research is to make a systematic, factual, and accurate picture or painting about the facts, propertiesand relationships between the phenomena being investigated. Qualitative BMetode is a research procedure thatproduces descriptive data in the form of written or spoken words from observable behavioral people. Datacollection techniques are the most strategic step in research, because the main purpose of a study is to obtaindata. Data Reduction, Data Display and Conclusion Drawing / Verification. The results of the study Land usechange in Lalat Regency, from 2021 to 2023, show signs of massive development. The area of buildings and roadshas increased, but on the other hand, the area of vegetation and green forests has decreased due to theincreasingly intensive land conversion. The local government of Langkat Regency should immediately realize apolicy on the protection of agricultural land for food crops in Langkat Regency so that it can prevent theconversion of agricultural land for food crops, through accelerating the realization of activities and includingfarmer groups in deliberations for development so that they can achieve the goal of protecting agricultural landfor sustainable food crops.